2017
DOI: 10.18043/ncm.78.6.357
|View full text |Cite
|
Sign up to set email alerts
|

Responding to a Community's Concern

Abstract: background A 2007 national report identified North Carolina’s Edgecombe County as having among the highest breast cancer incidence and mortality rates nationally, motivating the initiation of a task force and other local efforts to address the problem. The goal of this study is to examine county breast cancer characteristics before and after the report, including whether geographic variation may mask racial disparities in this majority African American community. method With guidance from community partners,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Another study, which examined occupational exposure to diesel exhaust, found that while there was no increased risk of overall breast cancer, diesel exhaust did elevate the risk of early-onset ER-tumors. This study emphasizes the need for further research into the relationship between air pollution exposure and the risk of ER-breast cancer [55].…”
Section: Discussionmentioning
confidence: 91%
“…Another study, which examined occupational exposure to diesel exhaust, found that while there was no increased risk of overall breast cancer, diesel exhaust did elevate the risk of early-onset ER-tumors. This study emphasizes the need for further research into the relationship between air pollution exposure and the risk of ER-breast cancer [55].…”
Section: Discussionmentioning
confidence: 91%